2021
DOI: 10.7150/thno.56059
|View full text |Cite
|
Sign up to set email alerts
|

Prodromal neuroinflammatory, cholinergic and metabolite dysfunction detected by PET and MRS in the TgF344-AD transgenic rat model of AD: a collaborative multi-modal study

Abstract: Mouse models of Alzheimer's disease (AD) are valuable but do not fully recapitulate human AD pathology, such as spontaneous Tau fibril accumulation and neuronal loss, necessitating the development of new AD models. The transgenic (TG) TgF344-AD rat has been reported to develop age-dependent AD features including neuronal loss and neurofibrillary tangles, despite only expressing APP and PSEN1 mutations, suggesting an improved modelling of AD hallmarks. Alterations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 103 publications
4
54
3
Order By: Relevance
“…The (Ji et al, 2008(Ji et al, , 2021Maeda et al, 2011;Jacobs and Tavitian, 2012;Mirzaei et al, 2016;Ishikawa et al, 2018;Tournier et al, 2019Tournier et al, , 2020Barron et al, 2020;Takuwa et al, 2020;Chaney et al, 2021;Fairley et al, 2021;Leng and Edison, 2021;, and third generation [ 18 F]GE-180, etc. (Eckenweber et al, 2020;Chaney et al, 2021;Palleis et al, 2021).…”
Section: Translocator Proteinmentioning
confidence: 99%
“…The (Ji et al, 2008(Ji et al, , 2021Maeda et al, 2011;Jacobs and Tavitian, 2012;Mirzaei et al, 2016;Ishikawa et al, 2018;Tournier et al, 2019Tournier et al, , 2020Barron et al, 2020;Takuwa et al, 2020;Chaney et al, 2021;Fairley et al, 2021;Leng and Edison, 2021;, and third generation [ 18 F]GE-180, etc. (Eckenweber et al, 2020;Chaney et al, 2021;Palleis et al, 2021).…”
Section: Translocator Proteinmentioning
confidence: 99%
“…Several studies have reported a reduced N-acetylaspartate/creatine ratio [ 148 , 149 ] and a lower glutamate level in APP/PS1 mice compared to wild-type mice [ 121 ]. Different metabolic profiles have also been demonstrated in animal models harboring both Aβ and tau pathologies, including 3 × Tg mice [ 153 ], 5 × FAD mice [ 152 ], APP/PS2/Tau mice [ 155 ], and TgF344 rats [ 146 ] ( Table 2 ). Lee et al demonstrated a 35% decrease in the availability of metabotropic glutamate receptor 5 measured by PET; a decrease in the levels of glutamate, N-acetylaspartate, and taurine; and an increase in the level of lactate by 1 H MRS in 5 × FAD mice compared to wild-type at 5 months-of-age [ 152 ].…”
Section: Neurochemical Changes Detectionmentioning
confidence: 99%
“…Several studies have reported reduced N-acetylaspartate /creatine ratio [125] and [124], lower glutamate levels [123] in APP/PS1 mice compared to wild-type mice. In animal models haboring both Aβ and tau pathology, including 3×Tg [129], 5×FAD mice [130], APP/PS2/Tau mice [131] and TgF344 rat [132] (Table 2). Lee et al demonstrated a 35 % decrease in the availability of metabotropic glutamate receptor 5 measured by PET and a decrease in glutamate, N-acetylaspartate and taurine, levels and an increase in lactate level by 1 H MRS in 5×FAD mice compared to wild-type at 5 months-of-age [130].…”
Section: Mrsmentioning
confidence: 99%
“…5×FAD mice [135] MRS TgF344 rats [132] J20 mice [109] APP/PS1 mice [121][122][123][124][125][126] 5×FAD mice [130] 3×Tg mice [129] APPswe mice [127,128]. APP/PS2/Tau mice [131] TASTPM mice [131,167] APP/PS1 mice [105,125,164,168,236] McGill-R-Thy1-APP rats [162] mice [250,251] APP-Au mice [252] 3×Tg mice [93,165,253] APPswe mice [244] APP/PS1KI mice [166] APP/TTA mice [254] DKI APP/PS1 mice [184] 3×Tg mice [188] qMTI APPswe mice [178] DTI TgF344 rats [183] APPswe mice [175,178,186,255] PDAPP mice [176] App NL-G-F knock-in mice [72] APP/PS1 mice [123,171,179,187,189,256] APP23 ...…”
Section: Declaration Of Interestmentioning
confidence: 99%